Extreme rainfall sensitivity in convective‐scale ensemble modelling over Singapore. (28th July 2019) - Porson, Aurore N.; Hagelin, Susanna; Boyd, Douglas F.A.; Roberts, Nigel M.; North, Rachel; Webster, Stuart; Lo, Jeff Chun‐Fung
Abstract : A convective‐scale ensemble system was developed to predict the occurrence of heavy convective rainfall around Singapore with a focus on the prediction of high‐impact events. The new ensemble SINGV‐EPS has been nested within two global ensembles, MOGREPS‐G (UK Met Office) and EC‐ENS (ECMWF). Predicting the occurrence of convective rainfall in an area such as Singapore is challenging and this article discusses the use of the convection‐permitting ensemble to characterize the uncertainties in the prediction of such localized heavy rainfall. First, verification of wind, temperature, and precipitation is performed for a month‐long period to assess the relative performance of each ensemble. This reveals differences, but no robust signal to say one is better than the other. The results are not statistically significant and not all variables are consistently better with one ensemble or the other. Secondly, the precipitation characteristics of SINGV‐EPS are analysed from probabilities of precipitation and variability among the ensemble members. SINGV‐EPS is sensitive to the choice of the global ensemble providing the initial conditions and boundaries. The results suggest there is benefit, in some cases, from combining the two ensembles. Thirdly, the spread of the ensemble precipitation is analysed using the dispersion Fractions Skill Score (dFSS). We compare the impact of the initial perturbations and the perturbations in lateral boundary conditions in both nesting options. The initial perturbations dominate in the beginning of the forecasts, with influence up to T+24 h, and are associated with an upscale growth of the uncertainties. The impact of the parent ensemble and lateral boundary conditions dominate at the end of the forecast and tend to influence larger scales more. Abstract : (a) Radar at [0800 UTC‐1100 UTC] on 30 October, (b) neighbourhood ensemble probability (NEP) of accumulated rainfall 0800‐1100 UTC on 30 October to exceed rain amounts of 6 mm over the 3 h for EC‐SINGV, and (c) UM‐SINGV. The simulations are initialized at 1500 UTC 29 October.